Minimum Wage Systems and Earnings Inequalities: Does Institutional Diversity Matter? - Andrea Garnero; Stephan Kampelmann; Francois Rycx (Institute for the Study of Labor (IZA), 2014)
This paper explores how the diversity of minimum wage systems affects earnings inequalities within European countries. It relies on the combination of (a) harmonized micro-data from household surveys, (b) data on national statutory minimum wages and coverage rates, and (c) hand-collected information on minimum rates from more than 1,100 sectoral-level agreements across Europe. The analysis covers 18 countries over the period 2007-2009. Empirical results confirm the intuition of many practitioners that the combination of sectoral minimum rates and high coverage of collective bargaining can, at least for earnings inequalities, be regarded as a functional equivalent to a binding statutory minimum wage at the national level. Regression results suggest indeed that both a national statutory minimum wage and, in countries with sectoral-level minima, a higher collective bargaining coverage are significantly associated with lower levels of (overall and inter-industry) wage inequalities and a smaller fraction of workers paid below prevailing minima. Several robustness checks confirm these findings.
Keywords: J31; J33; J51; 330; wage inequality; collective bargaining; minimum wage systems; Europe